2001
DOI: 10.3354/meps217093
|View full text |Cite
|
Sign up to set email alerts
|

Bay anchovy Anchoa mitchilli in Narragansett Bay, Rhode Island. I. Population structure, growth and mortality

Abstract: Population structure, growth and mortality of Anchoa mitchilli were evaluated in Narragansett Bay (Rhode Island, USA), an estuary near the northern extent of this species' broad latitudinal range. The Narragansett Bay population was dominated by young fish (Age 1 and young-ofthe-year, YOY); no fish were found to have survived a third winter. Growth rates were rapid, particularly during the first year of life, and annual mortality rates were estimated at > 90%. A von Bertalanffy growth model fit to length-at-ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
5

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 16 publications
1
7
0
5
Order By: Relevance
“…The maximum growth rate was 5 £ 10 ¡4 mm/min, which was five times the average growth rate of 0.07 mm/d reported for Bay Anchovy (Lapolla 2001). The realized growth rates in model simulations were much lower than the maximum and were comparable to the observed averages because few cells in the model environment allowed for maximum growth (i.e., most values of G c,r were < 1.0).…”
Section: Model Processessupporting
confidence: 57%
See 2 more Smart Citations
“…The maximum growth rate was 5 £ 10 ¡4 mm/min, which was five times the average growth rate of 0.07 mm/d reported for Bay Anchovy (Lapolla 2001). The realized growth rates in model simulations were much lower than the maximum and were comparable to the observed averages because few cells in the model environment allowed for maximum growth (i.e., most values of G c,r were < 1.0).…”
Section: Model Processessupporting
confidence: 57%
“…The maximum mortality rate was 4.2 £ 10 ¡5 per minute, which was five times the average annual mortality rate of 2.17 reported for Bay Anchovy (Lapolla 2001). As with growth, the realized mortality rates in simulations were comparable to observed averages because model individuals rarely experienced maximum mortality.…”
Section: Model Processesmentioning
confidence: 48%
See 1 more Smart Citation
“…However, differences in sardine length-at-age between recruitment areas such as south Biscay, north Portugal and the Gulf of Cadiz-north Morocco cannot be explained by migration. Instead, these differences suggest a latitudinal gradient in growth across the northeastern Atlantic, as observed for several temperate fish species, including clupeoids (Conover and Present, 1990;Lapolla, 2001). Latitudinal growth trends may have a genetic basis (countergradient growth variation; Conover and Present, 1990) as a consequence of selection pressures related to temperature seasonality and winter survival (Conover, 1992); increased juvenile growth enables populations to sustain longer, colder and often resource-poorer winters at higher latitudes and large body size increases the ability to store energy to reproduce in the beginning of the next growing season.…”
Section: Discussionmentioning
confidence: 94%
“…Newberger & Houde (1995) reported that sex ratios for this species are not well understood. Unbalanced sex ratios (female or male favoured) have been found in other engraulids, although there is no clear explanation for this phenomenon (Lapolla, 2001). The regional fluctuation of sex ratio in engraulids may relate to their physiological state: either the spawning period on one side and the inactivity period of the sexual cycle on the other (Sinovcic, 2000).…”
Section: Introductionmentioning
confidence: 99%